The Implementation of Lean Lean Sigma (LSS) on Canvassing Registration Process of Business Agencies Over Indonesian National Health Insurance (BPJS Kesehatan) South Jakarta Branch - Teguh Wijaya; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
The method of Lean Lean Sigma (LSS) today is not only used in manufacturing industries however it is continuing to keep developing in various sectors such as countries who use it in the governmental sector. Here, Indonesian National Health Insurance (BPJS Kesehatan) as Public Legal Entity which organizes the Health Insurance continued to make efforts to improve the coverage towards the achievement of universal membership or Universal Health Coverage (UHC) which should have been reached on January 1st, 2019, the achievement of participation in the Business Wage Recipient Participant segment is not in line with the target. Thus, the participant registration process is carried out using the Canvassing method where officers make visits from one business entity to another in accordance with the results of observations and pre-research interviews the process has weaknesses in this case there is a waste in the process, among others transportation, waiting, Over Processing and Defect, improvement that will be done is with Lean Sigma method by defining, measuring, analysing, increasing, and controlling DMAIC (Define, Measure, Analyse, Improve, Control) and the LCM (Lean Consumption Map) method. In this research, we use qualitative research method and interviews with internal and external correspondence, and the purpose of this study is to improve the Canvassing process and we found that this process is able to improve the Canvassing process.